The copper scroll, 3Q15 : a reevaluation : a new reading, translation and commentary - Lefkovits, Judah K. (Studies on the Texts of the Desert of Judah, 2000)
This volume deals with the Copper Scroll, an almost two thousand year old cryptic proto-Mishnaic Hebrew Dead Sea document. It is the largest known ancient text to have ever been recorded on metal. The Introduction covers the nature and site of the discovery, opening of the two brittle oxidized copper rolls, deciphering the text, controversy about genuineness of the content, et cetera The in-depth study presents the primary major studies, and offers a new reading, translation, and interpretation, including alternatives, as well as detailed studies of some unique aspects. The analysis is based on Rabbinical Jewish sources originating largely in the same historical era. This results into a more reliable interpretation of the Copper Scroll which probably originates from the Priestly leaders of Jerusalem, and contains a list of the hidden treasures of the Second Temple before its destruction by the Romans.